Land use change and urban heat islands in the seaside town of Kribi (Cameroon): Vulnerability and adaptation strategies - Philippes Mbevo Fendoung; Fabrice Armel Mvogo Moto; Marie Brigitte Makuate (European Scientific Journal, ESJ, 2024)
Urban heat islands (UHIs) are a pervasive manifestation of climate change in cities worldwide. In African coastal cities, often situated in low-lying areas with stagnant air, rapid demographic growth, and irreversible land-use changes, the proliferation of heat islands poses significant risks to vulnerable urban populationsa. This study investigates the interplay between land-use changes, the rise of heat islands, and the vulnerability of city dwellers in the seaside and port city of Kribi, Cameroon. It also explores effective adaptation strategies to mitigate the impacts of heat islands. Google Earth (GE) imagery from 2015, 2019, and 2023 is employed to assess land-use dynamics. Surface temperatures are analyzed for 2015, 2017, 2019, and 2023 using Landsat 8&9 imagery and Qgis 2.18 software. Meteoblue meteorological data is used to validate the findings. A GPS survey of air conditioners in Kribi, conducted using the SWMap mobile application, provides insights into stakeholder involvement and air conditioner categories. Additionally, a questionnaire administered to 200 city dwellers gathers information on their vulnerability to heat islands and mitigation strategies. Currently, surface temperatures in Kribi are projected to range between 26°C and 35°C between 2015 and 2023, with significant spatial variations in heat islands. To cope with these rising temperatures, most building occupants rely on air conditioning. Over 41% of surveyed city dwellers use air conditioning in their homes, with the highest proportion found in hotel and catering facilities (52%), followed by service offices (16%) and private homes (14%). Green space in Kribi has drastically declined between 2015 and 2023. In 2015, green space constituted 5,169 ha (83%), but by 2023, it had shrunk to 2,516 ha (43%), a loss of 261 ha. This decline was consistent between 2015 and 2019, with green space falling from 4,908 ha (83%) to 2,516 ha (43%).